PENERAPAN METODE INQUIRY PADA MATERI HIMPUNAN - Ana Istiani (Universitas Muhammadiyah Pringsewu, 2016)
This study aims to find the average of student learning achievement by implementing inquiry and expository method on sets material. To determine the difference between mathematics students learning achievement in the class that used inquiry method and the class that used expository method are using t test if they are fulfill two assumptions they were normal and homogeneous distributions. Based on the data analysis concluded that any mathematics learning achievement average differences obtained by inquiry method on the sets material. It showed that the students taught by inquiry method got better learning achievement average than the students taught by expository method. Keywords: inquiry method, expository method, students learning achievment